2022
DOI: 10.1093/cid/ciac498
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Binding and Angiotensin-Converting Enzyme 2 Binding Inhibition Is Significantly Reduced for Both the BA.1 and BA.2 Omicron Variants

Abstract: Background The rapid emergence of the omicron variant and its large number of mutations led to its classification as a variant of concern (VOC) by the WHO. Subsequently, omicron evolved into distinct sublineages (e.g. BA1 and BA2), which currently represent the majority of global infections. Initial studies of the neutralizing response towards BA1 in convalescent and vaccinated individuals showed a substantial reduction. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…To characterise the vaccination response after the third BN162b2 vaccination in 50 patients on maintenance haemodialysis, we had followed immunoglobulin levels longitudinally after the second dose of BNT162b2 using MULTICOV-AB, a multiplex immunoassay containing antigens from the Spike protein of SARS-CoV-2 and selected variants of concern ( 9 ). As a novel control group, 33 samples from healthcare workers with triple BNT162b2 vaccination were used for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To characterise the vaccination response after the third BN162b2 vaccination in 50 patients on maintenance haemodialysis, we had followed immunoglobulin levels longitudinally after the second dose of BNT162b2 using MULTICOV-AB, a multiplex immunoassay containing antigens from the Spike protein of SARS-CoV-2 and selected variants of concern ( 9 ). As a novel control group, 33 samples from healthcare workers with triple BNT162b2 vaccination were used for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…IgG binding and levels were analysed using MULTICOV-AB, a multiplex coronavirus immunoassay which contains the trimeric Spike B.1, its subdomains (S1, S2, RBD), nucleocapsid B.1 and RBDs of Delta and Omicron BA.1 antigens as previously described ( 9 , 19 ). Briefly, antigens were immobilised on spectrally distinct populations of MagPlex beads (Cat #MC10XXX-01, Luminex Corporation) either by EDC/s-NHS coupling ( 21 ) or by Anteo coupling (Cat #A-LMPAKMM-10, Anteo Tech Reagents) following the manufacturer’s instruction ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to declining antibody titers, booster vaccination was recommended to prolong protection against COVID-19. Furthermore, it has been shown that the antibodies that are developed after vaccines using the spike protein of a wild-type virus have a limited neutralization ability against new variants of the virus [ 33 ]. A third vaccination improves the antibody binding to the omicron variant [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plates were read on a FLEXMAP3D instrument (Luminex, United States) using the following settings: 80 µL (no timeout), 50 events, Gate 7500-15000, Standard PMT. Each plate included 3 wells with 150 ng/mL ACE2, 2 blank wells and 3 wells with a quality control (QC) sample as controls [25]. For each variant, ACE2 inhibition was calculated as a percentage, with 100% indicating maximum ACE2 inhibition and 0% indicating no ACE2 inhibition.…”
Section: Ace2 Binding Inhibition Assay Methodologymentioning
confidence: 99%